Široka opredelitev samozaposlitve v luči prepovedi diskriminacije na podlagi spolne usmerjenosti - Šuta, Živa (Podjetje in delo, 2023)
Under EU law, workers are afforded a high level of protection. Their dependent and subordinate position grants them the status of a weaker party and entitles them to a variety of rights recognised by both EU legislation and CJEU case law. In the twenty-first century, types of work that resemble the traditional employment relationship are emerging; however, their protection at the EU level remains unclear. Should the definition of a worker be expanded to include self-employed persons as well as those who provide goods and services on a regular basis and in a way that allows them to earn a living? This question becomes especially pressing when it is linked to the prohibition of discrimination. In the recent case TP (C-356/21), the CJEU addressed the issue of discrimination in (self-)employment, overturning the classic binary distinction between workers and self-employed persons. It clarified the scope of anti-discrimination protection enjoyed by self-employed workers, as well as the relationship between the contractual freedom of choice of contractual party and the prohibition of discrimination based on sexual orientation. The decision has been praised for its progressive interpretation that EU anti-discrimination law applies to all those who work, including self-employed individuals. This article analyses the decision C-356/21 and addresses the concerns of self-employed workers with the aim of framing their protection in EU anti-discrimination legislation and case law.
Keywords: delavci; delovna razmerja; delovno pravo; diskirminacija; pogodba o zaposlitvi; pravo EU; samozaposlitev; spolna usmerjenost; zakonodajne direktive; zunanji sodelavci